Gastric Residual Volumes Versus Abdominal Girth Measurement in Assessment of Feed Tolerance in Preterm Neonates: A Randomized Controlled Trial. (August 2018) - Thomas, Shemi; Nesargi, Saudamini; Roshan, Preena; Raju, Renjita; Mathew, Shiny; P., Sheeja; Rao, Suman
Abstract : Background: Preterm neonates often have feed intolerance that needs to be differentiated from necrotizing enterocolitis. Gastric residual volumes (GRV) are used to assess feed tolerance but with little scientific basis. Purpose: To compare prefeed aspiration for GRV and prefeed measurement of abdominal girth (AG) in the time taken to reach full feeds in preterm infants. Methods: This was a randomized controlled trial. Infants with a gestational age of 27 to 37 weeks and birth weight of 750 to 2000 g, who required gavage feeds for at least 48 hours, were included. Infants were randomized into 2 groups: infants in the AG group had only prefeed AG measured. Those in the GRV group had prefeed gastric aspiration obtained for the assessment of GRV. The primary outcome was time to reach full enteral feeds at 150 mL/kg/d, tolerated for at least 24 hours. Secondary outcomes were duration of hospital stay, need for parenteral nutrition, episodes of feed intolerance, number of feeds withheld, and sepsis. Results: Infants in the AG group reached full feeds earlier than infants in the GRV group (6 vs 9.5 days; P = .04). No significant differences were found between the 2 groups with regard to secondary outcomes. Implications for Practice: Our research suggests that measurement of AG without assessment of GRV enables preterm neonates to reach full feeds faster than checking for GRV. Implications for Research: Abdominal girth measurement as a marker for feed tolerance needs to be studied in infants less than 750 g and less than 26 weeks of gestation.